EXPERIMENTAL MODELING OF APOPTOSIS UNDER CONDITIONS OF STABLE STRONTIUM EXPOSURE - O. V. Dolgikh; N. V. Zaitseva; D. G. Dianova; A. V. Krivtsov; K. D. Starkova; E. A. Otavina (Медицинская иммунология, 2019)
Apoptosis is defined as a highly regulated form of programmed cell death with typical morphological and biochemical features. A variety of factors, including heavy metals, may influence the intensity of programmed cell death. The aim of the work was to simulate apoptosis in an in vitrosystem under the conditions of stable strontium exposure. The children’s population consuming drinking water with high strontium (Sr2+) content (n = 49) was observed. The level of lymphocyte apoptosis was determined with flow cytometry technique, by means of labeled annexin V-FITC conjugate (AnnV-FITC) and propidium iodide (PI) staining. AnnV-FITC+PI- cells were regarded as early apoptotic forms, whereas late apoptotic and/or necrotic cells were AnnV-FITC+PI+. The isolated leukocytes were incubated with Sr2+ at a concentration of 7.0 mg/l, the maximal permitted concentration (MPC) for water of aqueous objects, for 4 hours at 37 ºC. Expression of CD95 and p53 apoptosis markers was performed by flow cytometry using labeled monoclonal antibodies.In vitroexposure to strontium was associated with significantly decreased expression of apoptosisregulating factors, i.e., membrane marker CD95 and intracellular transcription protein p53, 1.56- and 1.68-fold, respectively. Meanwhile, we revealed a significantly (4.68-fold) decreased amounts of AnnV-FITC+PI--cells, as well as a statistically significant (1.35-fold) increase of the AnnV-FITC+PI+-cells. Moreover, the amounts of AnnV-FITC+ PI--lymphocytes in all samples were below the physiological ranges and control values. The number of samples with higher contents of AnnV-FITC+PI+-lymphocyte exceeding the established standards and control values, was 30.8%. Thus, it has been experimentally proven that strontium, at a concentration corresponding to MPC for water objects may significantly inhibit cell death along apoptotic pathways, with switching to necrotic cell death mechanisms, according to phosphatidylserine contents, as detected by annexin V binding test. The data have revealed an ability of strontium to have a significant effect upon the parameters of regulation and maintenance of cellular homeostasis, by influencing the apoptosis intensity, due to shifting a balance towards necrosis and reducing expression of apoptosis-regulating factors. The results of this study may be used in order to identify some marker indexes of immune disorders potentially induced by external influence of strontium upon human health under specific environmental factors.